An Integrated RME and PBL Mathematics E-Module for Vocational High School Learning: A Need Analysis - Hayuni, Argenti Agung; Murtiyasa, Budi; Setyaningsih, Nining (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
In this digital era, we can access information that we need easily. Including mathematics learning material. The are a lot if digital based learning materials that can be accessed anytime anywhere. However, the are still limited studies about developing mathematics e-modul as one of learning resources for vocational high school students. Therefore, this study investigates the need to develop An Integrated RME and PBL Mathematics E-Module for Vocational High School learning. This study is a descriptive survey involving 52 tenth grade students consist of 27 students from the Pharmaceutical Technology Expertise Field, 10 students from the Industrial Chemical Engineering Expertise Field, and 15 students from the Beauty and Spa Expertise Field, and also four mathematics teachers from four different vocational high schools with various expertise field in a city of Surakarta, Central Java, Indonesia. The data collection was conducted using printed questionnaires (for students) and online questionnaires (for teachers). The data was summarized and analyzed descriptively. Based on the data analysis, it can be concluded that there are still limited realistic problems in Indonesian mathematics textbook for vocational high school based on each expertise fields. Therefore, developing an integrated RME and PBL mathematics e-module is necessary. The characteristic of the integrated RME and PBL mathematics e-module are: (1) the e-module’s content should be presented in Bahasa Indonesia, providing realistic contexts by the certain expertise field and can also be from various expertise fields; (2) the learning activities should be carried out in groups, held inside or outside the classroom and involve problems that are related to the expertise field; (3) the learning media can be in the form of electronic and non-electronic media; (4) The assessment activities can be carried out in writing or authentic assessment.